X-FEM: An efficient algorithm for simulation of phase transition during prostate cryosurgery. (15th April 2020) - Tanwar, Sonam; Kumari, Preety
Abstract: Cryosurgery is a surgical technique to ablate abnormal tumor tissues with the help of extreme cold using cryogens such as liquid nitrogen, solid carbon dioxide, argon etc. This therapy may be used as a primary treatment for early prostate cancers effectively. During the process of freezing in cryosurgery, a phase transition occurs between the frozen tumor tissues and unfrozen surrounding tissues. The present study aims to showcase the efficiency of fixed grid X-FEM to numerically simulate the evolving phase transition front with time which further illustrates location & dimensions of ice ball generated after freezing. It has been observed that X-FEM with a fixed mesh is capable to capture phase transitions front and temperature fields accurately while traditional form of FEM requires adaptive re-meshing at each time step. From physician point of view, obtained temperature fields are really important to decide the extent of freezing, location of different cryoprobes, and numbers of cryoprobes to be used for a successful treatment.